An Empirical Analysis of Counter-Strike Weapon Cases as an Alternative Asset Class - Kokko, Elias (My University, 2026)
The significance of digital assets has increased rapidly in the 21st century, and investment objects tied to virtual environments have emerged as a new phenomenon in the investment landscape. As economic instability has intensified, interest in alternative investment assets has grown, particularly in assets whose development is not strongly linked to traditional financial markets. Digital commodities associated with gaming ecosystems have become more widespread, and their markets have expanded rapidly. Weapon cases in the game Counter-Strike represent such digital objects, whose value is determined by demand, supply, and player behavior. This thesis examines how Counter-Strike weapon cases behave as investment assets and what kinds of return, risk, and diversification characteristics are associated with them. The objective is to assess whether weapon cases can be considered an alternative asset class and how their return profile compares to other major investment assets. The analysis is based on key concepts from modern portfolio theory, neoclassical value theory, and research on digital assets. The empirical part of the thesis is based on data covering several weapon cases over a period of multiple years. The data have been collected from active markets to ensure that price development reflects actual trading activity. For comparison, data from a stock index, cryptocurrency markets, and gold markets are used. Based on the data, key return and risk metrics are constructed, along with a market-representative index that enables examination of the overall market segment. The results show that weapon cases constitute a market that differs clearly from traditional asset classes. They exhibit significant volatility, and there is substantial variation between individual assets. At the same time, high returns have been observed over the long term. Analysis at the market level indicates that diversification reduces the risks associated with individual assets and produces more stable development. Additionally, price movements have been found to be largely independent of the other examined markets, suggesting diversification benefits. In conclusion, Counter-Strike weapon cases can be viewed as an alternative asset class within the digital economy. Although individual assets involve high risk, diversification can improve the risk–return trade-off. Markets based on digital in-game items therefore provide an interesting foundation for further research and broaden the understanding of the field of alternative investments.

Digitaalisten omaisuuserien merkitys on kasvanut nopeasti 2000-luvulla, ja virtuaalisiin ympäristöihin sidotut sijoituskohteet ovat muodostuneet uudeksi ilmiöksi sijoitusmaailmassa. Talouden epävakauden lisääntyessä kiinnostus vaihtoehtoisiin sijoituskohteisiin on kasvanut, erityisesti sellaisiin, joiden kehitys ei ole vahvasti sidoksissa perinteisiin rahoitusmarkkinoihin. Peliekosysteemeihin liittyvät digitaaliset hyödykkeet ovat yleistyneet, ja niiden markkinat ovat laajentuneet nopeasti. Counter-Strike-pelin aselaatikot edustavat tällaisia digitaalisia objekteja, joiden arvo määräytyy kysynnän, tarjonnan sekä pelaajien käyttäytymisen perusteella. Tässä tutkielmassa tarkastellaan, miten Counter-Strike-aselaatikot käyttäytyvät sijoituskohteina ja millaisia tuotto-, riski- ja hajautusominaisuuksia niihin liittyy. Tavoitteena on arvioida, voidaanko aselaatikoita pitää vaihtoehtoisena omaisuusluokkana sekä miten niiden tuottoprofiili suhteutuu muihin keskeisiin sijoituskohteisiin. Tarkastelu perustuu modernin portfolioteorian, neoklassisen arvoteorian ja digitaalisten omaisuuserien tutkimuksen keskeisiin käsitteisiin. Tutkielman empiirinen osuus perustuu aineistoon, joka sisältää useita aselaatikoita usean vuoden ajalta. Aineisto on kerätty aktiivisilta markkinoilta, jotta hintakehitys heijastaa todellista kaupankäyntiä. Vertailua varten on hyödynnetty aineistoa osakeindeksistä, kryptovaluuttamarkkinoilta ja kultamarkkinoilta. Aineiston pohjalta on muodostettu keskeiset tuotto- ja riskimittarit sekä markkinaa kuvaava indeksi, joka mahdollistaa koko markkinasegmentin tarkastelun. Tulokset osoittavat, että aselaatikot muodostavat markkinan, joka poikkeaa selvästi perinteisistä omaisuusluokista. Niihin liittyy huomattavaa volatiliteettia ja yksittäisten kohteiden välillä esiintyy suurta vaihtelua. Samanaikaisesti on kuitenkin havaittu korkeita tuottoja pitkällä aikavälillä. Markkinatason tarkastelu osoittaa, että hajauttaminen tasoittaa yksittäisiin kohteisiin liittyviä riskejä ja tuottaa vakaampaa kehitystä. Hintakehityksen on lisäksi huomattu olevan pitkälti riippumatonta muista tarkastelluista markkinoista, mikä viittaa hajautushyötyihin. Johtopäätöksenä esitetään, että Counter-Strike-aselaatikot voidaan nähdä vaihtoehtoisena digitaalisen talouden omaisuusluokkana. Vaikka yksittäisiin kohteisiin liittyy korkea riski, hajauttaminen voi parantaa tuotto-riski-suhdetta. Digitaalisiin peliesineisiin perustuvat markkinat tarjoavat siten kiinnostavan lähtökohdan jatkotutkimukselle ja laajentavat ymmärrystä vaihtoehtoisten sijoituskohteiden kentästä.
Keywords: investments; investments (economics); finance; securities portfolios; risks; risk management; investment activities; security market; weapons; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance